2022
DOI: 10.3389/fgene.2022.817656
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aberrantly methylated differentially expressed genes and pro-tumorigenic role of KIF2C in melanoma

Abstract: Background: Skin Cutaneous Melanoma (SKCM) is known as an aggressive malignant cancer, which could be directly derived from melanocytic nevi. However, the molecular mechanisms underlying the malignant transformation of melanocytes and melanoma tumor progression still remain unclear. Increasing research showed significant roles of epigenetic modifications, especially DNA methylation, in melanoma. This study focused on the identification and analysis of methylation-regulated differentially expressed genes (MeDEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…The pan-cancer analysis findings indicated that CKS2 was highly expressed in most subtypes, and negatively correlated with OS, consistent with studies on adrenocortical carcinoma ( 31 ), lower-grade glioma ( 32 ), hepatocellular carcinoma ( 11 ), pancreatic adenocarcinoma ( 33 ), and skin cutaneous melanoma ( 34 ). Both several independent datasets and the IHC assay data confirmed upregulation of CKS2 in OSCC samples.…”
Section: Discussionsupporting
confidence: 85%
“…The pan-cancer analysis findings indicated that CKS2 was highly expressed in most subtypes, and negatively correlated with OS, consistent with studies on adrenocortical carcinoma ( 31 ), lower-grade glioma ( 32 ), hepatocellular carcinoma ( 11 ), pancreatic adenocarcinoma ( 33 ), and skin cutaneous melanoma ( 34 ). Both several independent datasets and the IHC assay data confirmed upregulation of CKS2 in OSCC samples.…”
Section: Discussionsupporting
confidence: 85%
“…A hypomethylated DNA was associated with specific protein upregulation. 30 By using immunohistochemistry staining, Liu et al 17 also reported CTLA-4 upregulation was associated with worse prognosis in ccRCC, whereas by using PCR, Tupikowski et al 19 reported polymorphism of CTLA-4 genes was associated with its aggressive course in ccRCC. Conversely with the previous studies, this study showed CTLA-4 expression in less aggressive subtype (pRCC) might be as high as RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous research revealed that the maintenance of circadian rhythmicity also involves epigenetic mechanisms [ 115 , 116 ]. Furthermore, the hypermethylation of promotor regions of circadian-cycle-dependent genes was observed in breast cancer cells [ 114 ], and melanoma [ 117 ], pan-renal cell carcinoma [ 118 ], cervical and esophageal cancer [ 119 ], and hepatocellular carcinoma cells [ 120 ].…”
Section: Melatonin and Its Role In Dna Methylationmentioning
confidence: 99%